Quality and storability of common beans in small-holders farm stores in Northern Tanzania: A multivariate analysis of agro-location, variety, and storage method effects. (December 2020) - Mutungi, Christopher; Chamwilambo, Musa; Masanja, Silvester; Massam, Caleb; Wayda, Peter; Tungu, Judith; Gaspar, Audifas; Bekunda, Mateete; Abass, Adebayo
Abstract: Incessant interactions between biotic and abiotic factors affect the physical quality of harvested, stored, and marketed beans. We investigated the interactions between variety and method of storage on the quality of harvested and stored beans in four contrasting agro-locations. Focus group discussions identified three varieties - a local speckled purple variety (Sp), and two improved ones: oval-shaped yellow (Oy) and round-shaped yellow (Ry), preferred by farmers for different reasons. Moisture, mechanical damage, bruchid infestation, bruchid damage, moldy/disease/discoloration (MDD), shriveling, impurities, and weight loss were analyzed at harvest and during storage in woven polypropylene (PP) or air-tight PICS bags. The average overall damage at harvest exceeded the limits set by local standards 2–3-fold, and the effect of variety was significant. The total damage of Ry (11.9 ± 0.7) surpassed that of Sp and Oy by factors of 2.8 and 2.5, respectively. Furthermore, the mean pre-storage bruchid infestation of Ry (1.4 Log counts/kg) surpassed Sp and Oy infestations by factors of 1.5 and 15, respectively. In storage, the quality was also dependent on variety. In the PP bags, the varietal differences were evident in all the attributes except MDD and insect damage, and the interaction between variety and location was significant on bruchid counts and bruchid damage. Variety Ry suffered more bruchid damage across all locations while Sp was attacked more in the cooler/humid agro-locations, compared to Oy, which was attacked more in the warmer/drier locations. With PICS bags, the varieties differed on the overall weight loss (Ry: 8.5 ± 4.1%, Sp: 2.3 ± 0.4%, Oy: 2.9 ± 2.7%). Results suggest that the air-tight storage bags are not suitable for some bean varieties. Further, careful pre-storage handling, andsorting for quality improvement, and actions to disinfest the beans before bagging need emphasis. In this regard, the cooler/humid agro-locations require closer attention. Highlights: Interaction effects of agro-location, variety, and storage methods on beans' quality investigated. Quality during pre-storage handling and storage was highly dependent on the variety. Interaction between variety and agro-location was significant in ordinary storage. Air-tight storage was found unsuitable for some varieties. Careful pre-storage handling and good practices to improve quality and storability emphasized.